2015
DOI: 10.1371/journal.pone.0131377
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Human Studies to Support a Quantitative Recommendation for Whole Grain Intake in Relation to Type 2 Diabetes

Abstract: BackgroundDue to the increasing evidence of their health benefits, whole grains are recommended for consumption worldwide. Such recommendations are, however, rarely quantitative. Our aim was to perform a quantitative evaluation of the relationship between whole grain consumption and the occurrence of type 2 diabetes (T2D) to support a recommendation on the daily consumption of whole grains.Methods and FindingsWe conducted a systematic review by searching three bibliographic databases. We included human studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…Compared with refined grain products that comprise mainly the endosperm, whole grain foods are rich in a wide variety of nutrients in the outer bran and germ layers: several vitamins, dietary fiber, minerals, and phytochemicals. [1] Many a prospective cohort studies and meta-analyses have linked a higher intake of whole grains and a decreased risk of cardiovascular disease (CVD), [24] type 2 diabetes, [5,6] and some types of cancers. [7,8] Human clinical trials have showed that consumption of whole grain foods have beneficial roles in total cholesterol and LDL-cholesterol, [9,10] glucose metabolism, [11] endothelial function, [12] and inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with refined grain products that comprise mainly the endosperm, whole grain foods are rich in a wide variety of nutrients in the outer bran and germ layers: several vitamins, dietary fiber, minerals, and phytochemicals. [1] Many a prospective cohort studies and meta-analyses have linked a higher intake of whole grains and a decreased risk of cardiovascular disease (CVD), [24] type 2 diabetes, [5,6] and some types of cancers. [7,8] Human clinical trials have showed that consumption of whole grain foods have beneficial roles in total cholesterol and LDL-cholesterol, [9,10] glucose metabolism, [11] endothelial function, [12] and inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses of prospective studies have consistently reported inverse associations between WG intake and type 2 diabetes (T2D), 811 cardiovascular diseases (CVD), 8, 12, 13 and certain cancers, 1416 which are among the major global causes of death. However, existing findings on WG intake and mortality remain largely inconclusive.…”
mentioning
confidence: 99%
“…Chanson-Rolle et al 2015 8 Aune et al 2013 4 Ye et al 2012 9 increased heterogeneity is inevitable because of the wide variation in study design. Differences in study design include number of participants, duration of the study, age, sex, body mass index, total energy intake for the participants, method of dietary whole grain intake measurements, and source and types of whole grains (eg, whole grain cereals, brown bread, and brown rice).…”
Section: Citation Matrix For Meta-analyses On Type 2 Diabetes Incidmentioning
confidence: 99%